Pengaruh Kesadaran Wajib Pajak Dan Pemahaman Wajib Pajak Terhadap Penerimaan Pajak Dengan Kepatuhan Wajib Pajak Sebagai Variabel Intervening Pada Kpp Pratama Surabaya Karang Pilang - Febiani Tevia Permana; Endah Susilowati (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
The purposes of this research are to analyze the influence awareness of paying taxes and taxpayer understanding to tax income, directly or indirectly, by taxpayer compliance as an intervening variable. The population in this research were individual taxpayers in pratama tax service office Surabaya Karang Pilang. The sampling method used in this research is simple random sampling that obtained 100 research respondents. The data analysis technique used in this research is Structural Equation Modeling (SEM) with WarpPLS 6.0 as the software. The results showed that : (1) taxpayer awareness has a positive effect on taxpayer compliance, (2) taxpayer understanding has a positive effect on taxpayer compliance, (3) taxpayer awareness has a positive effect on tax income, (4) taxpayer understanding has a positive effect on tax income, (5) taxpayer compliance has a positive effect on tax income, (6) taxpayer compliance capable as an intervening variable taxpayer awareness to tax income, (7) taxpayer compliance capable as an intervening variable taxpayer understanding to tax income